Peutz-Jeghers Syndrome: A Comprehensive Literature Review with Illustrative Case Series - Hemalatha, Ganjala; Ramya, Valaparla; Pragna, Gunde; Mitha, Pasam Madhu; Muskan, Shaik; Lavanya, Korikani; Kavya, Galanki Arundathi; Rao, Gajula Ram Nageswara; Sandhya, Vadduri (Indian Journal of Pharmacy Practice, 2026)
Peutz-Jeghers Syndrome (PJS) is a rare autosomal dominant disorder characterized by hamartomatous gastrointestinal polyps and mucocutaneous pigmentation, with an increased risk of malignancy. To present a comprehensive overview of PJS through literature review and illustrative case series highlighting clinical presentation, diagnosis, and management. Five illustrative cases are presented demonstrating varied clinical manifestations of PJS. Common presenting features included recurrent abdominal pain, anemia, and mucocutaneous pigmentation. Two cases presented with intussusception requiring surgical intervention, while others were managed with endoscopic polypectomy and surveillance. One case demonstrated malignant transformation, emphasizing cancer risk. Histopathological findings in all cases confirmed hamartomatous polyps. PJS exhibits diverse clinical presentations ranging from mild symptoms to severe complications. Early recognition and regular surveillance are essential to prevent morbidity and detect malignancy at an early stage.
Keywords: Case series; Gastrointestinal polyposis; Hamartomatous polyps; Intussusception; Mucocutaneous pigmentation; Peutz-Jeghers Syndrome; STK11 mutation